Tree species composition, biomass and carbon stocks in two tropical forest of Assam. (July 2015) - Borah, Maina; Das, Dhrubajyoti; Kalita, Jatin; Deka Boruah, Hari Prasanna; Phukan, Barsha; Neog, Bijoy
Abstract: Tropical forests store higher above ground biomass (AGB) and AGB carbon (AGBC) than any other forest ecosystems. In the present study the tree composition, diversity, dominance and carbon stocks in the AGB and soil of tropical forests viz., the Gibbon wildlife sanctuary (GWS) and the Kholahat reserve forest (KRF) of Assam, India were assessed. Soil sampling, tree survey, girth above 1.3 m height of plants >10 cm girth of plants were assessed in 1000 m 2 quadrate. Allometric model for moist forest stands was used to determine AGB and AGBC. A total of 71 and 108 different tree species belong to 32 and 42 families were found in the GWS and KRF, respectively. In the GWF, the Shannon diversity index (1.22) and the Simpson index (0.085) were significant, while for the KRF these indices were insignificant. The basal area, AGB and AGBC in the GWS and KRF were 62.49–90.29 m 2 ha −1, 135.30–146.42 Mg ha −1, and 67.64–73.21 Mg ha −1, respectively. The average soil carbon stock (SOC) in the upper, middle and lower layers was 57.74–78.44 kg m −2, 39.22–64.93 kg m −2 and 30.32–42.86 kg m −2, respectively, in the GWS and KRF. However, compared to GWS, a higher AGB and AGBC were found in KRF. This finding reveals that the higher AGB, AGBC and SOC in the KRF were due to old growth matured forest with big and diverse tree species. Highlights: Tropical forest store more biomass carbon than any other forest. Assam, which covers 3.5% of India's total forest mostly of tropical forest. We assess tree composition, AGB and AGB carbon in Gibbon and Kholahat forest of Assam. Shannon diversity and Simpson index were significant while for Kholahat it was insignificant. Gibbon is secondary evergreen/semi evergreen patch vegetation while Kholahat is old growth forest.